(untitled) (Scientific journal of the Fergana State University, 2023)
The article shows that the use of morphological means in Uzbek children’s poetry is one of the most important tools in revealing the unique beauty of children’s speech, the richness of emotions, emotionality and expressiveness. Examples are given from poetic works that refer to morphological poetics.